IDELA in the promotion of Latin American thought - Valverde-Morales, Marcelo (2026)
This essay reviews some of the fundamental historical actions, based on which the Institute of Latin American Studies (IDELA) of the National University of Costa Rica (UNA) has promoted and contributed to the field of Latin American thought. It has validated as our own the legacy of the intellectual Joaquín García Monge and his work in promoting intellectual networks, publishing and education, tasks that were highlighted with the creation of the Cátedra Joaquín García Monge, first of its kind formulated at the UNA.